2019
DOI: 10.1111/jace.16904
|View full text |Cite
|
Sign up to set email alerts
|

Giant dielectric behavior of monovalent cation/anion (Li+, F) co‐doped CaCu3Ti4O12 ceramics

Abstract: Giant dielectric behavior and electrical properties of monovalent cation/anion (Li+, F−) co‐doped CaCu3Ti4O12 ceramics prepared by a solid‐state reaction route were systematically investigated. Substitution of Li+ and F− led to a significantly enlarged mean grain size. A reduced loss tangent (tanδ ~0.06) with the retainment of an ultra‐high dielectric permittivity (ε′ ~7.7‐8.8 × 104) was achieved in the co‐doped ceramics, while the breakdown electric field and nonlinear coefficient of CaCu3Ti4O12 ceramics were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 51 publications
2
16
0
Order By: Relevance
“…This result confirmed that this phase was not in the CCTO grain. Thus, this area can be considered a Cu-rich phase, as has been reported in the literature [7,27]. Other elements were dispersed in both the CCTO and secondary phase grains.…”
Section: Resultssupporting
confidence: 60%
“…This result confirmed that this phase was not in the CCTO grain. Thus, this area can be considered a Cu-rich phase, as has been reported in the literature [7,27]. Other elements were dispersed in both the CCTO and secondary phase grains.…”
Section: Resultssupporting
confidence: 60%
“…A great increase in grain size due to doping was also reported in earlier published papers. [6][7][8]27 This vastly increased grain size of the doped samples, compared to CCTO ceramic, might have been caused by liquid-phase sintering mechanisms. Generally, a liquidphase can form at junctions between particles or GBs, resulting in a much increased diffusion rate.…”
Section: Resultsmentioning
confidence: 99%
“…In advanced ceramics, essential raw materials for producing electronic components have been widely researched in this important eld. Focusing on capacitor applications, the colossal dielectric properties of polycrystalline ceramics, such as the codoped TiO 2 , 1,2,17,[20][21][22] codoped SnO 2 , 3 and ACu 3 Ti 4 O 12 (A ¼ Ca, [4][5][6][7][8][9]24 Cd, [10][11][12] Sm 2/3 , 13 Y 2/3 , 14 Na 1/2 Y 1/2 , 15 Na 1/2 Sm 1/2 , 25 Na 1/3 Cd 1/3 Y 1/3 16 ceramics have been developed and reported in the literature. Preserving high 3 0 values in these ceramics is the primary objective, followed by reducing loss tangents (tan d) and enhancing temperature/frequency stability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations